Penerapan E- Modul Model Flip Berbasis PBL Terhadap Kemampuan Berpikir Kritis Dan Kemampuan Memecahkan Masalah Mata Pelajaran IPA Di Sekolah Dasar - Ubaidah, Nur; Wazni, Muhammad Khairul; Supiyati, Sri (Universitas Hamzanwadi, 2024)
This research aims to determine the effect of implementing a flip model e-module based on Problem Based Learning (PBL) on students' critical thinking and problem solving abilities in science subjects. The research method used was a quasi-experiment with a non-equivalent control group design. The subjects of this research were class IV students who were divided into two groups, namely the experimental class which used the PBL-based flip model e-module and the control class which did not use the e-module. Data was obtained through tests of critical thinking abilities and problem solving abilities which were analyzed using the one-way MANOVA test. The results of the research show that there is a significant effect of implementing the PBL-based flip model e-module on students' critical thinking and problem-solving abilities. The average critical thinking ability score in the experimental class was 71.75, higher than the control class which only reached 65.75. Meanwhile, the average problem solving ability in the experimental class reached 72, while in the control class it was only 60. Statistical analysis showed a significance value of 0.040 for critical thinking ability and 0.028 for problem solving ability, which shows a significant difference between the two groups.